TEKNOLOGI SMART EGGS INCUBATOR HYBRID UNTUK MENINGKATKAN PRODUKTIVITAS TERNAK AYAM - Khairul Muttaqin; Nasruddin Nasruddin; Nurul Fadillah; Ahmad Ihsan (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Kampung Selamat is one of the villages in Tenggulun Sub-district, Aceh Tamiang Regency, which is 45 kilometers from the capital city of Aceh Tamiang. Most of the villagers work as farmers and breeders. Kampung Selamat has high natural resource potential in the livestock sector, but has not been managed optimally. The Dunia Ternak Unggas group is one of the productive livestock business groups in Selamat village that was established in 2019 with the main focus of developing chicken farming. The problems faced by the World Group of Poultry in business development include; (1) The process of hatching chicken eggs is still conventional, which still requires mother chickens; (2) It takes a long time to hatch eggs; (3) The risk of eggs not successfully hatching is still very large; (4) The process of checking chicken eggs is still manual, namely looking directly at the location; and (5) limited land so that the layout of hatching chickens is uncontrollable. To face these challenges, it is necessary to develop hybrid smart eggs incubator technology that can significantly help livestock business groups in increasing chicken productivity and simplifying the breeding process. The steps of implementing the activity include the socialization stage, design and manufacture of tools, as well as training, mentoring, and application of these devices. The results of the implementation of this activity indicate that the level of user satisfaction with the IoT-based hybrid Egg Hatching Machine Incubator reached an average of 87.93%. This fact illustrates that this tool is a solution that is worth adopting to increase efficiency in the hatching process of chicken eggs and has the potential to produce a positive impact on chicken farming and provide solutions to the obstacles faced by livestock business groups.